An inverse mean-line design method for optimizing radial outflow two-phase turbines in geothermal systems. (May 2021) - Li, Hongyang; Rane, Sham; Yu, Zhibin; Yu, Guopeng
Abstract: Radial outflow two-phase turbine (ROTPT) is an impulse two-phase turbine used for total flow systems in applications like geothermal fields to utilize the two-phase geofluid energy effectively. This paper presented a one-dimensional nonequilibrium inverse mean-line design method of ROTPT. With prescribed pressure and blade angle distributions, the averaged geometry and flow parameters in the rotating impeller channels were derived along the flow direction, the pressure distribution was formulated on the pressure side (PS) and the suction side (SS), and performance parameters were deduced in the implementation of the presented algorithm, including torque, output power, efficiency, etc. By using the design method, a ROTPT for a geothermal system was constructed. The flow field of the ROTPT was simulated in CFX using the thermal phase change model, which was validated by experimental results. By evaluating the averaged distribution and examining the three-dimensional flow, it was suggested that the presented design was consistent with the averaged flow in ROTPT. Meanwhile, there were three-dimensional effects in the rotating channel causing the deviation between the design and CFD results. This paper provides a nonequilibrium solver for designing ROTPTs but also can bolster the development of two-phase flow with the phase change in curved rotating channels. Highlights: The presented method can derive flow and geometry for radial outflow two-phase turbines. Resulting parameters can agree with the average flow of experimentally validated CFD tool. Three-dimensional flow causes the deviation between design and CFD.